Relationship between the optic nerve sheath diameter and lumbar cerebrospinal fluid pressure in patients with normal tension glaucoma - Pircher, A; Montali, M; Berberat, J; Remonda, L; Killer, H E (Eye (London), 2017)
Purpose To investigate on the relationship between the optic nerve sheath diameter (ONSD) and the lumbar cerebrospinal fluid pressure (CSF-p) in Caucasian patients with normal tension glaucoma (NTG). Patients and methods Retrospective analysis of medical records of patients with open-angle glaucoma in the period from 2005 to 2015 from the Ophthalmology Department, Cantonal Hospital Aarau, Switzerland was performed. A total of 38 patients (mean age 68.6±11.3 years, 21 females and 17 males) fulfilled the diagnostic criteria of NTG and underwent computed tomography (CT) of the orbit and lumbar puncture (LP). In total, 38 age- and gender-matched Caucasian subjects (mean age: 68.9±10.9 years) without known ON diseases served as controls for ONSD measurements. ONSDs were measured at a distance of 3 mm from the posterior globe and lumbar CSF-p was related to the measurements. Statistical analysis was performed by using the independent two-tailed t -test and the non-parametric Spearman's correlation test. Results The mean ONSD in NTGs measured 6.4±0.9 mm and in controls 5.4±0.6 mm. The difference between NTGs and controls showed statistical significance ( t -test: P <0.000). The mean CSF-p in NTG was 11.6±3.7 mm Hg. There was no statistical significant correlation between ONSD and CSF-p (Spearman's correlation coefficient ρ =0.06, P =0.72). Conclusions This study demonstrates enlarged ONSDs and normal lumbar CSF-p in 38 Caucasian NTG patients. As enlarged ONSDs generally are associated with increased intracranial CSF-p, these results can be explained by a disturbed communication of CSF-p between the intracranial and intraorbital subarachnoid spaces.